Sudden Intrabulbar Amyloid Increase Simultaneously Disrupts Olfactory Bulb Oscillations and Odor Detection - Rebeca Hernández-Soto; Keila Dara Rojas-García; Fernando Peña-Ortega (Neural Plasticity)
There seems to be a correlation between soluble amyloid beta protein (Aβ) accumulation in the main olfactory bulb (OB) and smell deterioration in both Alzheimer’s disease (AD) patients and animal models. Moreover, this loss of smell appears to be related to alterations in neural network activity in several olfactory-related circuits, including the OB, as has been observed in anesthetized animals and brain slices. It is possible that there is a correlation between these two pathological phenomena, but a direct and simultaneous evaluation of the acute and direct effect of Aβ on OB activity while animals are actually smelling has not been performed. Thus, here, we tested the effects of acute intrabulbar injection of Aβ at a low dose (200 pmol) on the OB local field potential before and during the presence of a hidden piece of smelly food. Our results show that Aβ decreases the power of OB network activity while impairing the animal’s ability to reach the hidden food. We found a strong relationship between the power of the OB oscillations and the correlation between OBs and the olfactory detection test scores. These findings provide a direct link between Aβ-induced OB network dysfunction and smell loss in rodents, which could be extrapolated to AD patients.